NorthBEAT: exploring the service needs of youth experiencing early psychosis in Northern Ontario - Cheng, Chiachen; Nadin, Shevaun; Bohonis, Hafsa; Katt, Mae; Dewa, Carolyn S. (Frontiers in Health Services, 2023)
Introduction Early Psychosis Intervention (EPI) is critical for best outcomes. Among 369 diseases, psychosis is among those causing the greatest disability. Evidence-based interventions for youth in early stages of psychosis (EPI programs) have prevented chronic disability. Yet, EPI is frequently inaccessible for youth living in rural communities. Moreover, Indigenous youth often face more precipitous situations given inadequate staffing, and culturally unsafe care. The NorthBEAT (Barriers to Early Assessment and Treatment) project sought to understand the service needs of youth with psychosis in Northern Ontario. The goals were: (1) to describe the mental health of a subset of adolescents receiving EPI care; (2) examine Indigenous youth as a significant and vulnerable population; (3) to understand the barriers and facilitators for Indigenous and non-Indigenous youth receiving EPI. Methods Mixed methods (structured and narrative interviews) included: psychometric scales interviews with youth, and narrative interviews with youth, their family, and service providers Data validation workshops were held with participants. Results Structured interviews with 26 youth (M = 17 years) found the participants functioning moderately well with duration of untreated psychosis ranging from 1 to 96 months (M = 26 months). No significant differences were found in functioning or duration of psychosis between Indigenous and non-Indigenous youth. Narrative interviews were conducted with 18 youth, 11 family members, and 14 service providers. Identified barriers were a lack of knowledge about psychosis among service providers, a disconnected system leading to delays in treatment, help not wanted by youth, expansive geographical context. Service needs were: finding the right point of access, support for families, pre-crisis intervention, reduced stigma for youth and their families, and an EPI approach to care. Discussion Rural and northern youth face similar barriers to accessing EPI as urban youth. However, northern youth face additional unique challenges due to expansive geographical context, limited resources and lack of knowledge about services.